Emptiness in the study of emotions in the teaching-learning process of reading-writing during the COVID-19 pandemic - Martí-González, Mariacarla; Barrasa, Angel; Belli, Simone; Espinel, Johana; Da Costa, Silvia; López-Granero, Caridad (Frontiers in Psychology, 2022)
The teaching-learning process of reading and writing has great relevance in the psycho-emotional and socio-psychological development of school-age children. This is an exercise in which they develop imagination, attention and memory capacity and through this process the management of emotions and sensitivity and capacity of apprehension of reality. The crisis derived from the COVID-19 pandemic transformed reality in an unprecedented way in the recent history of humanity and the educational context was shaken by all these changes. With confinement, the teaching-learning process of reading and writing, which is designed to take place in person, had to be developed in a hybrid or online way, which was a major challenge for teachers and families and, of course, also for children who were in the process of learning. One of the aspects that was blurred in this context was the role of the teacher, which in this case is one of the most important elements, to achieve adequate learning of reading and writing. On one hand, the teacher is in charge of helping to manage the emotions derived from the learning process itself and, on the other hand, he is a key figure so that this is not only technical learning but also contributes to the child’s socio-emotional development. The aim of this study was to analyze the impact of the socio-psychological changes that have occurred in the educational context since the COVID-19 pandemic on the emotions linked to the teaching process, learning of reading and writing through a systematic review of the studies carried out on the subject, in order to provide recommendations for face-to-face learning in the post-COVID-19 era. A systematic review strategy was devised and the literature search was conducted. The search was conducted using ERIC, Dialnet, Scopus, WoS, EBSCO, and Google Scholar databases. This systematic review took place during the month of May 2022. The results show that given the scarce presence of empirical studies on the subject, the objective has only been partially met. However, a systematic review of the studies carried out on the subject. For the identification of recommendations in the development of face-to-face learning in the post-covid era, it has been possible to identify some ideas of interest for future curricular designs in primary school students who are immersed in learning to read and write.